The Brent market : an analysis of recent developments - Bacon, R (Oxford Institute for Energy Studies, 1986)
The recent history of the informal market for North Sea Brent blend has been of great interest to those studying commodity markets in general and the oil market in particular. Two aspects of this market gives it this important position. First, the very rapid growth inactivity in the Brent market means that for much of 1985 an average of at least 400 deals a month were being made. With each deal being for a lot size of 600,000 barrels of oil at around $25 a barrel the total turnover i n 1985 was at least $72 billion. The second feature of the market is that it operates as an informal forward market. There is no central clearing agency, as in a futures market, and so each deal is done directly between agents.